The European arrest warrant in the case law of the Court of Justice - Patricio, Helena (2014)
A key factor in the creation of a European area of freedom, security and justice is the principle of mutual recognition, which the Framework Decision 2002/584/JHA of 13 June 2002, for the first time, comprehensively implemented in the field of judicial cooperation in criminal matters. The Court of Justice of the European Union has greatly contributed to the understanding of the Framework Decision, accentuating its goals and enhancing its guiding principles, which are the mutual recognition of judgments in the different Member States of the European Union and mutual trust that should settle among them, for the creation of the said area. The West judgment of 28 June 2012, C-192/12 PPU, on urgent preliminary ruling procedure, aptly illustrates the impact of this case law, highlighting the role of this procedure, implemented on 1 March 2008.